Co-Evolution of Capabilities and Industry: The Evolution of Mutual Fund Processing - Levinthal, Daniel A.; Myatt, Jennifer (Strategic Management Journal, 1994)
The resource view of the firm has made substantial progress in identifying what attributes of a firm may provide a source of competitive advantage; however, the literature has far less to say about the emergence of these distinctive capabilities. We develop a simple framework based on the role of positive feedback effects of market activity, organizational factors that cause a firm to focus on a particular capability trajectory, and lastly the role of managerial choice with respect to anticipated feedback effects, which we term feedforward effects. We apply this framework to the emergence of competitive positions in the mutual fund-processing business from its inception to 1984.